Marie Antoinette. Season 2 [videorecording (DVD)] - Schüle, Emilia, 1992-; Cunningham, Louis, 1998-; Archer, Jack (Actor) (PBS, 2025)
In Season One, Marie Antoinette emerged as a triumphant Queen of France. Without her mother, she knows she is all alone as she faces both her enemies and any obstacles that await. Now, in Season Two, bigger and stronger enemies are waiting in the wings to destroy her. The higher Marie Antoinette climbs in the estimation of the French people, the greater the threats are against her. At the height of their power, Marie Antoinette and Louis face an unprecedented financial crisis. The incessant attacks of Provence and Chartres against the royal couple stir up the hatred of the nobles while disastrous consequences loom with the Diamond Necklace Affair. From Versailles to the Palais-Royal, the revolt rumbles on.